Legislation and the Constitutional Court: Reconciling Constitutional Justice and Democratic Accountability in Comparative Constitutional Law: Legislation and the Constitutional Court: Reconciling Constitutional Justice and Democratic Accountability in Comparative Constitutional Law - Muhammad Rum Siolimbona; Hedwig Adianto Mau; Sineenart Suasoongnern (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
The dynamic relationship between legislation and constitutional courts has become a key issue in modern constitutional law. Legislation, reflecting democratic legitimacy, often faces challenges when political majorities pass laws that may threaten constitutional rights and the rule of law principles. Conversely, constitutional courts act as guardians of constitutional supremacy, ensuring that laws align with fundamental constitutional values. This study uses a normative juridical and comparative approach, analyzing constitutional texts, legislation, and landmark judicial decisions from Indonesia, Germany, South Africa, and South Korea. Through content analysis, comparative legal methods, and hermeneutic interpretation, the research shows that constitutional courts worldwide do not just correct unconstitutional laws but also play a constructive role in fostering democratic accountability. The findings emphasize that the relationship between legislation and constitutional courts should not be seen as adversarial; rather, it is a dialectical and symbiotic interaction that promotes constitutional democracy. The novelty of this research lies in its global comparative perspective, moving beyond country-specific analyses and suggesting a conceptual framework for understanding how legislative legitimacy and constitutional justice reinforce each other. This study contributes both to theoretical debates in comparative constitutional law and offers practical recommendations for improving judicial review and legislative processes in democratic systems.